Implementasi Diversi terhadap Anak yang Berkonflik - Alhakim, Abdurrakhman; Siahaan, Bonita Maharani; Febriyani, Emilliya (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The protection and welfare of children in the criminal justice system is the main focus of efforts to find alternative solutions that do not involve children in formal legal processes, such as imprisonment, which can have a negative impact on their development. Law No. 11/2012 on Juvenile Criminal Justice System (SPPA Law) implements the concept of restorative justice through a diversion system. This study aims to understand the regulation of diversion under the SPPA Law and how it is implemented in the Batam District Court in handling children involved in legal problems. The research method used is empirical juridical. The implementation of diversion in Batam District Court aims to achieve restorative justice which emphasizes on recovery, providing opportunities, and children's awareness of their mistakes. The goal is to ensure children's growth and development rights are guaranteed by law. Although the implementation of diversion in Batam District Court is in accordance with the provisions of the SPPA Law, there are obstacles that make it less effective. From 2019 to 2022, 18 cases were eligible for diversion, but only 4 cases were successfully resolved using this method, while 14 other cases failed due to various obstacles and constraints accompanying its implementation.